PLURALISME HUKUM KEWARISAN DI INDONESIA (Mazahib, 2013)
In Indonesia, there are at least three types of inheritance laws still exist and live in the midst of society, namely: inheritance laws based on Islamic law, customary inheritance law is very pluralistic circumstances, and inheritance laws based on the Book of the Law Civil Law (Civil Code) / BW. Configuration of the various laws that will certainly bring further consequences. Heirs can be faced with (at least) three legal options. Though each of the inheritance law systems have fundamental differences about the causes of inheritance, heirs sequence, and part heir. In the perspective of the law, inheritance law diversity is its own treasure or wealth for the nation of Indonesia, but this would lead to legal pluralism legal uncertainty. If allowed to continue not impossible contradiction inheritance law will be driving the increasingly rampant family tension and conflict. Moreover, at this time increasingly individualized family relationships where people are more concerned with material including inheritance. Without reducing the excess of each legal heir, in the spirit of harmony and the rule of law, there would be time national heritage laws can be used as a legal reference.